Revealing the relationship between photoelectrochemical performance and interface hole trapping in CuBi2O4 heterojunction photoelectrodes. Issue 41 (28th September 2020) - Song, Angang; Levine, Igal; van de Krol, Roel; Dittrich, Thomas; Berglund, Sean P.
Abstract : CdS, BiVO4, and Ga2 O3 buffer layers were tested between CuBi2 O4 and TiO2 in heterojunction photoelectrodes. Photoelectrochemical analysis and modulated surface photovoltage spectroscopy revealed that interface hole traps impacted device performance. Abstract : p-Type CuBi2 O4 is considered a promising metal oxide semiconductor for large-scale, economic solar water splitting due to the optimal band structure and low-cost fabrication. The main challenge in utilizing CuBi2 O4 as a photoelectrode for water splitting, is that it must be protected from photo-corrosion in aqueous solutions, an inherent problem for Cu-based metal oxide photoelectrodes. In this work, several buffer layers (CdS, BiVO4, and Ga2 O3 ) were tested between CuBi2 O4 and conformal TiO2 as the protection layer. RuO x was used as the co-catalyst for hydrogen evolution. Factors that limit the photoelectrochemical performance of the CuBi2 O4 /TiO2 /RuO x, CuBi2 O4 /CdS/TiO2 /RuO x, CuBi2 O4 /BiVO4 /TiO2 /RuO x and CuBi2 O4 /Ga2 O3 /TiO2 /RuO x heterojunction photoelectrodes were revealed by comparing photocurrents, band offsets, and directed charge transfer measured by modulated surface photovoltage spectroscopy. For CuBi2 O4 /Ga2 O3 /TiO2 /RuO x photoelectrodes, barriers for charge transfer strongly limited the performance. In CuBi2 O4 /CdS/TiO2 /RuO x, the absence of hole traps resulted in a relatively high photocurrent density and faradaic efficiency for hydrogen evolution despite the presence of pronounced deep defect states at the CuBi2 O4 /CdS interface. Hole trapping limited the performance moderately in CuBi2 O4 /BiVO4 /TiO2 /RuO x and strongly in CuBi2 O4 /TiO2 /RuO x photoelectrodes. For the first time, our results show that hole trapping is a key factor that must be addressed to optimize the performance of CuBi2 O4 -based heterojunction photoelectrodes.